The Effects of Return on Investment and Corporate Governance Mechanism of the Issuers Manufactur Stock Price In Indonesia Stock Exchange - Endang Masitoh Wahyuningsih, Rochmi Widayanti (GEMA, 2015)
This study to examine the effect of corporate governance mechanisms are proxied by institutional ownership and combining with fundamentals such as return on investment (ROI). Given this research are expected to know which factors have an influence on the value of the stock price is proxied by cloce pricing. The sample used in this study is a manufacturing company, located in the Jakarta Stock Exchange and using purposive sampling method. The data analyzed are from the audited financial statements from 2010 to 2013 and obtained from the JSE, ICMD, BAPEPAM, UNS and Corner Exchange and other financial information from the internet. Meanwhile, to test the hypothesis used multiple linear regression test so as to know the effect of the independent variable (KpIn and ROI) on stock prices. The results of this study indicate that simultaneous ROI affect the companys stock price, while institutional ownership has no effect.The results of this study are expected to be used as information for investors and issuers of variable institusioanl ownership and fundamental information that can affect the stock price of a company, whereas for academic instructional materials to strengthen the capital market courses and financial management